عورت کی تعلیم : تاریخی اسلامی رویہ: Women’s Education: Historical Islamic Behavior (Al-Qamar, 2019)
Behavior of Islam and Muslims about women education has been a debated subject. Some people argue that Islam and Muslims do not give women their right of Education. This paper explores the historical Muslim behavior towards women education. It shows the importance of female education and commendable historical Muslim behavior about women education. It argues that Islam compels the Muslim society to provide education to both men and women equally. Islamic sacred text and Muslim Civilization always seem to encourage women Education. In the course of Muslim history we find many famous Muslim women excelling in their fields of knowledge. ʻĀysha Siddīqa, ʻĀisha bint Sa’d Ibn Abī Waqās, Rabiʻah Bint Mu’awwad, Umm ‘Atiyyah etc. are some examples from early Muslim history in referred perspective.
Keywords: Education; Women; Islam; Muslims; Behavior